Utilization of satellite data in determining hydropower potential to support energy security in new capital city region of Indonesia - Kuntoro, Arno Adi; Roesbianto, Azman Syah Barran; Farid, Mohammad; Kardhana, Hadi; Rohmat, Faizal Immaddudin Wira; Rizaldi, Akbar; Kusuma, Muhammad Syahril Badri; Adityawan, Mohammad Bagus; Wahid, Ahmad Nur (Frontiers in Earth Science, 2024)
The relocation of the national capital from DKI Jakarta to the East Kalimantan region and its people migration requires energy escalation. This project will require an additional 1,555 MW of electricity from existing conditions. In line with Indonesia's clean energy transition, this need can be addressed by developing renewable energy infrastructure, particularly hydropower. This study evaluates the hydropower potential in the Mahakam River using a run-of-river scheme. Given the limited availability of hydro-climatological ground stations, satellite data such as CFSR-TRMM, SRTM DEM, DSMW, and land-cover data were utilized, supported by the SWAT rainfall-runoff model for hydrological analysis. Data calibration was applied, and discharge results were analyzed using a new diversion algorithm to estimate potential power output. Innovative resampling of headrace arrangements was introduced to mitigate potential hydropower conflict sites. Social factors, including protected areas and water transportation routes, were also incorporated to minimize land disputes. The study identified 25 mini-hydropower sites and 16 micro-hydropower sites with a total capacity of 105.4 MW and 9 MW, respectively. These small-scale hydropower systems could supply 3.4% of the projected electricity demand for the new capital city called Nusantara (IKN), and potentially reduce annual carbon emissions by approximately 480,000 tons. The use of satellite data requires meticulous attention to ensure that data acquisition and processing yield reliable results while accurately reflecting field conditions. This research position also provides an initial overview of energy transition strategies in the IKN area through hydropower development and the subsequent potential assessment.